Penggunaan dan Kepuasan Nasabah Terhadap Layanan E-Banking di BSI - Zubaili, Zubaili; Zulkarnaini; Hamdani , Rizki; Cahyani , Dwi; Husna; Putri, Erlina; Hajar, Siti (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi, 2023)
Currently, banks have issued a service called Electronic Banking (E-Banking). Where one of the services of E-Banking is Internet Banking which functions as an alternative to conducting banking transactions online using the Internet. Internet Banking makes it easier for customers to do online banking transactions, both financial transactions and non-financial transactions, except for making deposit transactions or cash withdrawals. But when using Internet Banking services, is there control or a chaotic system? Therefore, this article explains the reasons why customers use E-Banking services, the benefits perceived by customers, what are the obstacles faced by customers and suggestions or input on BSI E-Banking. Then in this article also provides an explanation of the experience of using E-Banking by customers. This article also explains the advantages and disadvantages of the E-Banking system. So that bank customers who wish to use Internet Banking services gain knowledge and can choose a bank that provides better and safer Internet Banking service security and can reduce disturbances in the E-Banking service system